Penilaian Keaslian Bangunan De Tjolomadoe Menggunakan Instrumen Nara Grid - Ayu Ratna Pitaloka; Yusfan Adeputera Yusran (RUAS (Review of Urbanism and Architectural Studies), 2019)
Physical and non-physical changes that occur in the new building of the ex-Tjolomadoe Sugar Factory is one of the concrete evidences of conservation that implementing adaptive reuse approach in saving this 157-year-old factory construction. Once, this building actively serves as a sugar factory for many decades and then was abandoned for 20 years. Until in 2017, it was revitalized by changing its function from the factory to a cultural center and commercial area, then changed its name to “De Tjolomadoe”. This study aims to assess the authenticity of De Tjolomadoe by using the Nara Grid instrument. The research itself runs by combining qualitative and quantitative method with observations, strengthened by interviews and capturing opinions through questionnaire on various groups of people ranging from the layman to the experts. The result then has analyzed into the Nara grid table. It show that the authenticity of the building is still maintained. There are some changes especially in the interior to accomodate new functions, but does not eliminate the spatial form. The building structure also has strengthened and the addition of architectural elements and interior ornaments to make it more attractive to visitors.